2011
DOI: 10.1063/1.3644156
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of nitrogen atoms in SiC-SiO2 interfaces studied by electrically detected magnetic resonance

Abstract: The microscopic behavior of nitrogen atoms in the SiO 2-SiC interface regions of n-channel lateral 4 H-SiC metal-oxide-semiconductor field effect transistors (MOSFETs) was studied using low-temperature electrically detected magnetic resonance spectroscopy and other techniques. The results show that nitrogen atoms eliminated shallow interface states observable at 20 K and further diffused into the channel region of the MOSFETs as shallow donors. These two behaviors enable nitrogen atoms to change the channel co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 17 publications
0
53
0
Order By: Relevance
“…Their amounts exceeded over 1×10 14 cm -2 , which is three orders of magnitude larger than the reduction in D it (10 10 −10 11 cm -2 ) [4]. The secondary change is the doping of shallow nitrogen donors into the channel region [8]. The amount of the doped nitrogen donors was estimated to be ~10 12 cm -2 [9], which is comparable to the concentration of free carriers in the channel region [8].…”
Section: Understanding the Characteristics Of Si-face Mos Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their amounts exceeded over 1×10 14 cm -2 , which is three orders of magnitude larger than the reduction in D it (10 10 −10 11 cm -2 ) [4]. The secondary change is the doping of shallow nitrogen donors into the channel region [8]. The amount of the doped nitrogen donors was estimated to be ~10 12 cm -2 [9], which is comparable to the concentration of free carriers in the channel region [8].…”
Section: Understanding the Characteristics Of Si-face Mos Interfacesmentioning
confidence: 99%
“…In fact, we have studied shallow interface states in Si-face MOSFETs using low-temperature electrically detected magnetic resonance (EDMR) spectroscopy [8]. In addition to EDMR, interfacial nitrogen atoms have been characterized by X-ray photoelectron spectroscopy (XPS) [4].…”
Section: Understanding the Characteristics Of Si-face Mos Interfacesmentioning
confidence: 99%
“…In another study where we applied electrically detected magnetic resonance to the channel region of (0001) 4H-SiC MOSFETs, 15 we found that nitrogen shallow donors were doped in the channel region after post-nitridation annealing. This result can be explained by supposing that some part of the fixed nitrogen atoms are incorporated into the SiC layer during nitridation where they occupy substitutional sites (i.e., carbon sites), and are activated as shallow donors.…”
mentioning
confidence: 99%
“…5 Å) SiO 2 layer formed on SiC during the annealing by sustained etching in hydrofluoric acid. The same group [7] demonstrated by the electrically detected magnetic resonance technique that shallow donor levels can be associated with a fraction of the incorporated N atoms. However, information on the electrical activation of the incorporated nitrogen and on the depth extension of the nitrogen profile is still lacking.…”
Section: Introductionmentioning
confidence: 99%